The Effect of Oil Prices on Azerbaijan’s Economy (2009–2018) - Sarkhanov , Teymur (Economy of Regions, 2022)
Since oil plays an important role in the economy of Azerbaijan, the events in the global oil market deeply affect the national economy. Moreover, the COVID-19 pandemic influenced the economy of Azerbaijan, in which oil and gas have a significant place. In April 2020, the price of one barrel of oil on the world market fell to 1. One reason for this was the decrease in oil demand due to the lockdown regime implemented by many countries due to the rapid outbreak of the COVID-19 pandemic, and another reason was that the OPEC (Organization of the Petroleum Exporting Countries) countries could not agree on reducing oil production. The aim of this research is to show the impacts of oil prices on gross domestic product (GDP) of Azerbaijan, the growth rate of GDP, and the amount of oil production in Azerbaijan in 2009-2018. The hypothesis of the research is that oil prices seriously influence the economy of Azerbaijan and there is a correlation between the growth rate of Azerbaijan’s gross domestic product and the oil prices. The quantitative method was used as a key research method. The data used in the analysis of this study were collected according to the literature scanning method, which is one of the data collection techniques. Further, descriptive statistics technique, was used to analyse the data. The findings show that the changes in oil prices in 2009-2018 directly affect the Azerbaijan’s gross domestic product, the growth rate of GDP, and the amount of oil production in Azerbaijan. Thus, as oil prices increase, the growth rate of the country’s gross domestic product and GDP increase and decrease as oil prices decrease.